URGENSI HADITS TARBAWI DALAM PENDIDIKAN ISLAM - Fatoni, Ahmad; Pratama, Angga; Raba Pramodana, Dimas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Islamic education today faces serious challenges, including moral degradation, value disorientation, and a spiritual crisis among students. One of the proposed solutions is the integration of Tarbawi Hadiths into the education system. Tarbawi Hadiths refer to a collection of hadiths related to pedagogy and character development, which serve as an essential source in Islamic education. This study aims to analyze the urgency of Tarbawi Hadiths in Islamic education, particularly in shaping students with noble character, critical thinking skills, and adaptability to changing times. The research employs a library research method with a qualitative approach and thematic analysis. Data were collected from various literature on Tarbawi Hadiths and primary hadith sources such as Sahih Bukhari and Sahih Muslim. The results indicate that Tarbawi Hadiths function not only as a theoretical foundation for Islamic education but also as a practical guide for educators in shaping students' morality. Furthermore, Tarbawi Hadiths act as both pedagogical and moral instruments capable of addressing contemporary educational challenges. By internalizing the values embedded within Tarbawi Hadiths, the educational process can balance cognitive and affective aspects while fostering a more inclusive and harmonious community.